Adenovirus Type 21 Outbreak Among Lung Transplant Patients at a Large Tertiary Care Hospital. (31st July 2018) - Philo, Sarah E; Anderson, Benjamin D; Costa, Sylvia F; Henshaw, Nancy; Lewis, Sarah S; Reynolds, John M; Jayakumar, Jayanthi; Su, Yvonne C F; Gray, Gregory C
Abstract: Here we summarize an April 2016, 7-patient cluster of human adenovirus (HAdV) infections in a cardiothoracic surgery intensive care unit. We show that the patients were infected with a single HAdV21b type. Rapid HAdV typing diagnostics and effective antiviral interventions are needed for immunocompromised patients suffering from HAdV infections.